Efficacy and Safety of Blood Stasis Based Herbal Medicine for Patients with Traffic Accident: A Prospective Observational Study - Sung Min Bong; Hyo Rim Jo; Woo Seok Jang; Seong Kyeong Choi; Won Suk Sung; Chan Yung Jung; Seung Deok Lee; Kyung Ho Kim; Eun Jung Kim (MEDrang Inc., 2020)
Background Blood stasis (BS) is commonly used for pattern identification in traumatic injuries, including traffic accidents (TAs). Various studies have identified the efficacy of Korean medicine treatments for TA patients, but studies focusing on the BS-based herbal medicine (BSHM), including Tongdo-san (TDS), are rare. Methods This was a single-center, prospective observational study, conducted from August 24th, 2018 to December 27th, 2018, which included 40 TA patients. Participants underwent routine Korean medicine treatments including acupuncture, electronic moxibustion, cupping, physical therapy, and herbal medicine. In the herbal medicine treatment, participants took BSHM with more than 3 days including taking TDS. The primary outcome measures were the scores from a 100 mm visual analogue scale (VAS) and numerical rating scale (NRS). Secondary outcome measures included scores from EuroQol-5 dimension (EQ-5D) and EQ-VAS questionnaires, the BS and cold/heat indices, and safety assessments. Results There were significant improvements in the VAS, NRS, EQ-5D, EQ-VAS scores, and BS index after treatment. In the sub-analysis, VAS, NRS, EQ-5D, and EQ-VAS scores were higher in groups with a higher BS index. The moderate and severe BS index groups showed more improvement than the minor BS index group, and there was a significant difference in the EQ-5D scores. There was no significant differences observed in cold/heat index groups scores. Conclusion BS is associated with TA-related symptoms. BSHM, including TDS, may significantly reduce BS, pain, and discomfort.